Development of Guided Inquiry-Oriented Science Interactive E-Module on Wave and Disaster Themes - Prasetyaningsih, Prasetyaningsih; Vitasari, Mudmainah; Wilujeng, Insih (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2022)
This research aims at measuring the validity product of the developed science interactive e-book. The research method used is research and development, with a 3-D development model which is a modification of the 4-D model proposed by Thiagarajan (1974). The stages used are defining, planning (design) and developing (develop). To measure the product validity, a validation questionnaire assessed by two expert lecturers and three science teachers was employed. The development of teaching materials in the form of science interactive e-books is scored 81% and is considered valid to be limited trial test in junior high school level. The limited trial test is scored 34.55 which is considered as good category. Therefore, the developed e-modules can be used as learning resources on wave and disaster themes.